2020
DOI: 10.1093/ndt/gfaa089
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality risk associated with citric acid- and acetic acid-based bicarbonate haemodialysis: a historical cohort propensity score-matched study in a large, multicentre, population-based study

Abstract: Abstract Background Citric acid-based bicarbonate dialysate (CiD) is increasingly used in haemodialysis (HD) to improve haemodynamic tolerance and haemocompatibility associated with acetic acid-based bicarbonate dialysate. Safety concerns over CiD have been raised recently after a French ecological study reported higher mortality hazard in HD clinics with high CiD consumption. Therefore, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A multicenter, historical cohort propensity score-matched study of adult incident hemodialysis patients found no statistically significant difference in mortality between patients dialyzed with CAD and patients dialyzed with AAD. 13 A recent retrospective observational study conducted in France included a 5-year follow-up period and demonstrated that mortality risk is not increased with the use of CAD (relative to dialysate without citrate). 34 In a recent, multicenter, randomized crossover study, CAD with 3 mEq/L calcium had a positive effect on the calcification propensity during dialysis treatment relative to conventional AAD solutions containing 3 and 2.5 mEq/L calcium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter, historical cohort propensity score-matched study of adult incident hemodialysis patients found no statistically significant difference in mortality between patients dialyzed with CAD and patients dialyzed with AAD. 13 A recent retrospective observational study conducted in France included a 5-year follow-up period and demonstrated that mortality risk is not increased with the use of CAD (relative to dialysate without citrate). 34 In a recent, multicenter, randomized crossover study, CAD with 3 mEq/L calcium had a positive effect on the calcification propensity during dialysis treatment relative to conventional AAD solutions containing 3 and 2.5 mEq/L calcium.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that substituting CAD solutions for acetate-acidified dialysate (AAD) in bicarbonate dialysate could improve hemodynamic and dialysis tolerance, enhance biocompatibility with reduced extracorporeal thrombosis risk, and reduce the requirement for anticoagulation, which can be particularly important for patients at risk of bleeding. 13 CAD may also improve dialysis adequacy, presumably due to the non-systemic anticoagulant effects on the dialyzer. 14–16 A multicenter, prospective analysis of patients on hemodialysis treated with CAD demonstrated that CAD could reduce heparin doses while maintaining dialysis adequacy.…”
Section: Introductionmentioning
confidence: 99%
“…Of them, 371 were exposed at least 70% of the time spent on dialysis to citric acidcontaining dialysate (CiD70%). After propensity score matching, annual mortality was 11.43 [95% confidence interval (CI) 8.86-14.75] and 12.04 (95% CI 9.44-15.35) deaths/100 personyears in the CiD0% and CiD70% groups, respectively (P=0.80) (31). The second study, also in incident hemodialysis patients and after a median follow-up of 23 months, did not show any increased risk of mortality with the use of citric acid containing dialysate, despite higher comorbidities in the citric acid-exposed group (32).…”
Section: Discussionmentioning
confidence: 99%